Conceptualizing Academic Norms in Middle School: A Social Network Perspective. (May 2015) - McCormick, Meghan P.; Cappella, Elise
A wide body of research has documented the relationship between social norms and individual behaviors. There is growing evidence that academic behaviors in early adolescence—when most children begin middle school—may be subject to normative influence as well. However, the structure and composition of peer relationships within middle schools have yet to be fully incorporated into current conceptualizations of academic norms. A social network approach that considers the structure of students' friendship networks can be a useful framework for informing understanding of middle school academic norms. This article integrates research and theory on social norms and social networks to introduce a model to improve understanding of academic norms in middle schools. Implications for future research are discussed.